2002
DOI: 10.1002/art.10468
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory effect of retrovirally transfected interleukin‐10 on monosodium urate monohydrate crystal–induced acute inflammation in murine air pouches

Abstract: Objective. To investigate the role of interleukin-10 (IL-10) in the inflammatory response, the antiinflammatory effect of retrovirally transfected IL-10 was evaluated both in vitro and in vivo.Methods. A recombinant retrovirus containing the murine IL-10 gene was constructed using the pLXSN vector and was designated as LXSN-IL-10. Murine IL-10 was introduced into embryonic C57BL/6J fibroblast cells using LXSN-IL-10 to create C57-IL-10 cells. The effect of IL-10 in the culture supernatant of these cells was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Maximum induction occurred at 4 hours, and expression subsequently declined 8 hours after stimulation. We previously demonstrated increased expression of IL-1␤, macrophage inflammatory protein 2, and KC in infiltrating cells in this air-pouch model (18,19). The time course of TREM-1 mRNA expression closely resembles gene expression of inflammatory cytokines and chemokines.…”
Section: Resultsmentioning
confidence: 58%
“…Maximum induction occurred at 4 hours, and expression subsequently declined 8 hours after stimulation. We previously demonstrated increased expression of IL-1␤, macrophage inflammatory protein 2, and KC in infiltrating cells in this air-pouch model (18,19). The time course of TREM-1 mRNA expression closely resembles gene expression of inflammatory cytokines and chemokines.…”
Section: Resultsmentioning
confidence: 58%
“…Administration of neutralizing Abs directed against IL-8 (10), MCP-1 (12), and growth-related oncogene ␣ (13) significantly reduced MSU crystal-induced leukocyte accumulation, suggesting an important role for these chemokines in acute gout. In parallel, the use of the murine air-pouch model has further confirmed that MSU crystal-mediated leukocyte recruitment correlates with chemokine (macrophage inflammatory protein (MIP)-1␣/CCL3, MIP-2/ CXCL2, MCP-1 and KC/CXCL1) and myeloid-related protein (S100A8, S100A9, and S100A8/A9) release (8,14,15). Consistent with these data, MSU crystals activate the expression of a number of cytokines and chemokines in various types of leukocytes.…”
mentioning
confidence: 88%
“…In monocytes, MSU crystal administration results in the release of tumor necrosis factor-␣ (16), IL-1 (17), , and IL-8 (6). In macrophages, increased mRNA levels of tumor necrosis factor-␣, MIP-1␣, MIP-1␤, and KC (14) as well as of IL-␤ and MIP-2 (15) have been detected upon MSU crystal treatment. Similarly, neutrophils are known to respond to MSU crystals by secreting, among others, IL-1 (19), , and reactive oxygen species (21).…”
mentioning
confidence: 99%
“…18) The crystals were suspended in PBS at a concentration of 10 mg/ml. The crystals were sonicated to obtain rod-shaped crystals of uniform length (5 25 mm) and sterilized by autoclaving at 121°C for 30 min.…”
Section: In Vivo Evaluationmentioning
confidence: 99%